BORROWER’S CREDITWORTHINESS: CONTENT AND EVALUATION CRITERIA - Pohrishchuk , H. B.; Voloshchuk , R.Ye. (The actual problems of regional economy development, 2021)
Currently, lending allows not only to profit from attracting additional financial resources, but also to expand and develop business activity. Therefore, many businesses apply for additional funds to credit institutions. Under such conditions, creditworthiness becomes important, because the effective organization of the lending process will depend on its proper understanding and quality assessment. The need to study the essence of creditworthiness is explained both by the lack of consensus among scholars on the definition of this concept, and the further development of credit institutions, which, in turn, influence the content of this definition. The article is devoted to the study of legislative and scientific approaches to the essence of the borrower's creditworthiness, conducting a content analysis of this concept and determining on its basis the criteria for creditworthiness assessment.The specifics of scientific tasks being the subject of the research required the use of a complex of methods which enabled to carry out a content analysis of the term “creditworthiness” and identify the main criteria for the borrower's creditworthiness assessment. The article examines domestic legal documents, that determine the content of creditworthiness. The approaches to understanding the essence of this definition, which were distinguished by foreign and Ukrainian scientists, are considered. A content analysis of the concept of “creditworthiness” is performed. The characteristics of the main criteria, which are the basis for borrower’s creditworthiness assessment, is carried out. The study proved, that creditworthiness is characterized by a set of conditions that allow the lender to provide credit and the borrower to fulfill debt obligations in accordance with the terms of the loan agreement. It is substantiated, that the borrower's creditworthiness is assessed on the basis of criteria that take into account the internal and external environment of its operation. It is established that without the definition of these criteria and the assessment of creditworthiness in modern market conditions, the conclusion of a loan agreement is impossible.